MEASUREMENT OF ALMAMATER SUIT SUPPLY CHAIN PERFORMANCE IN SACIKA COOPERATIVE USING SCOR - Zahra Fikri Ayu Nirwana; Aruga Yudish Firmansyah; Syifa Nur Fadhilah; M Yoka Fathoni (STMIK Royal, 2024)
Abstract: SACIKA Cooperative, as a student cooperative at the Telkom Institute of Technology Purwokerto, provides almamater suit procurement services. Currently, the process of procuring and ordering almamater suits is faced with several obstacles, which results in students as customers feeling disadvantaged during the ordering process. Therefore, it is necessary to evaluate the performance of the supply chain at the SACIKA Cooperative in order to improve efficiency and suitability in the procurement of alma mater suits. This study aims to assess the performance of the alma mater suit supply chain at the SACIKA Cooperative using the SCOR Matrix. This type of research is descriptive quantitative, with data collection conducted through interviews and observations. Supply chain performance measurement is carried out using four attributes and matrices, namely Reliability with Perfect Order Fulfillment (POF), Responsiveness with Order Fulfillment Cycle Time (OFCT) Matrix, Agility with Cost of Goods Sold (COGS), and Assets with Cash-to-Cash Cycle Time (CTCCT) Matrix. The results showed the performance value of each matrix, namely POF of 96.47%, OFCT 1 day, COGS 92.94%, and CTCCT 8 days. Keywords: SCOR matrix; supply chain management; supply chain flow patterns Abstrak: Koperasi SACIKA, sebagai koperasi mahasiswa di lingkungan Institut Teknologi Telkom Purwokerto, menyediakan layanan pengadaan jas almamater. Saat ini, proses pengadaan dan pemesanan jas almamater dihadapi beberapa kendala, yang mengakibatkan mahasiswa sebagai pelanggan merasa dirugikan selama proses pemesanan. Oleh karena itu, perlu dilakukan evaluasi terhadap kinerja rantai pasok di Koperasi SACIKA guna meningkatkan efisiensi dan kesesuaian dalam pengadaan jas almamater. Penelitian ini bertujuan untuk menilai kinerja rantai pasok jas almamater di Koperasi SACIKA menggunakan Matriks SCOR. Jenis penelitian ini bersifat deskriptif kuantitatif, dengan pengumpulan data dilakukan melalui wawancara dan observasi. Pengukuran kinerja rantai pasok dilakukan dengan menggunakan empat atribut dan matriks, yaitu Reliability with Perfect Order Fulfillment (POF), Responsiveness with Order Fulfillment Cycle Time (OFCT) Matrix, Agility with Cost of Goods Sold (COGS), dan Assets with Cash-to-Cash Cycle Time (CTCCT) Matrix. Hasil penelitian menunjukkan nilai performansi masing-masing matriks, yaitu POF sebesar 96,47%, OFCT 1 hari, COGS 92,94%, dan CTCCT 8 hari. Kata kunci: matriks SCOR; manajemen rantai pasok; pola aliran rantai pasok